Microwave-Assisted Solvent Free Synthesis of Some 4,6-Dicinnamoyl Resorcinols - Ashok, D.; Shravani, D. (Asian Journal of Chemistry, 2010)
4,6-Dicinnamoyl resorcinols (2a-h) were synthesized in high yield (90-95 %) using a microwave-assisted solvent free condensation reaction of 4,6-diacetyl resorcinol (1) and aromatic/ heteroaromatic aldehydes under alkaline medium. Products were recrystallized from benzene. Synthesis of 4,6-dicinnamoyl resorcinols under microwave irradiation is found much easier and faster than conventional method.